Structural and weathering response of Aerogel foam-based sandwich composites - Lee, Gavin Ju-lian (Nanyang Technological University, 2020)
Silica Aerogels, renowned in the aeronautics and aerospace industry for its heat insulation properties as well as its low density, have traditionally been extremely expensive and tedious to reinforce to form composite structures capable of carrying loads. However, recent advancements in research has established gelatin as a suitable binder material to pre-synthesised Aerogel particles, capable of forming an Aerogel-based foam composite which retains its advantageous physical properties at a fraction of the cost. The purpose of this paper is to explore the possibilities of inculcating additives into the binder material so as to produce Aerogel-based foam composites with slightly different physical properties. Also, by means of a Universal Testing machine, to understand the mechanical response of Aerogel foam filled Nomex honeycombs when compressed in the out-of-plane direction, as well as the transverse direction. Samples were compressed in the out-of-plane direction until the onset of densification. Compression done along the transverse direction was carried out until 25mm displacement of the machine crosshead, as well as intermittent loading carried out at 15% deformation relative to the sample’s total height. The main focus being the mechanical improvements which the Aerogel foam was able to impart to the Nomex honeycomb. By using Aerogel foam as a filler material for different types of honeycomb material, the paper also aims to understand the weathering response of the Aerogel foam filled composite structures. The main purpose for this is to understand how the bond between the Aerogel foam and the corresponding core material disintegrates when exposed to water over a period of 72 hours. The samples are periodically removed from immersion to be dried and weighed, and the data collated for the change in mass would be used to evaluate bond disintegration over the entire period of the experiment.